Intangible Cultural Heritage Practices in Sacred Garden of Lumbini - Nyaupane, Pashupati (Journal of Lumbini Engineering College, 2024)
Similar to Mecca or Bethlehem, Lumbini is a significant pilgrimage center. UNESCO World Heritage Site Maya Devi Temple, which is situated close to a holy pool. This site has the archaeological remnants of brick structures built by Ashoka in the third century BC, as well as the discovery of a timber shrine from the sixth century BC. The ancient monastic remains at Lumbini, the sacred Bodhi tree, an ancient bathing pond, the Ashokan pillar, built by King Ashoka in 249 BC, and the Maya Devi Temple encompass the holy site. The sacred Bodhi tree, the Ashokan pillar, the Mayadevi Temple which is believed to be the place of the Buddha's birth and the remains of previous monasteries may all be found at Lumbini, a holy site. At the location, pilgrims from different nations chant and meditate from early dawn till early evening. Moreover, The Lumbini monastic zone is a model of meditation and spiritual living, enclosed away during its picturesque surroundings. The lessons of the Buddha, Siddhartha Gautama, are repeated in this place by the rhythm of devotion and reflection through life. The intangible cultural heritage of Lumbini, the sacred place of Lord Buddha's birth, is a living collection of rituals, ceremonies, and traditions. Spiritual practices such as ancient meditation processes, lively folk dances, oral traditions, and sacred ceremonies are examples of these cultural intangibles. Lumbini's intangible heritage demonstrates to the vast spiritual and cultural heritage of Buddhism, connecting and encouraging gratitude among Buddhists worldwide.